(untitled) (Proceedings of International Conference on Special Education, 2015)
This is a small ground work study that aims to give a base input to a more comprehensive investigation into the state of readiness of Malaysian public universities when it comes to taking in students with disabilities (referred to as OKUs – Orang Kelainan Upaya - in this paper). It is carried out by examining university websites to ascertain if OKU policies are in place. It also looks at whatever relevant write-ups relating to OKUs in universities. It has been found that general provisions on this group of people are available, but their implementation in universities, on the whole, still has a long way to go. There is also a dearth of local research on the fulfilment of the needs and requirements of OKUs in public universities, which means there is still much to do in this area